2018
DOI: 10.1016/j.trci.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor‐kappa B: Glucocorticoid‐induced leucine zipper interface analogs suppress pathology in an Alzheimer's disease model

Abstract: IntroductionGlucocorticoid-induced leucine zipper is a regulatory protein that sequesters activated nuclear factor-kappa B p65. Previously, we showed that rationally designed analogs of the p65-binding domain of glucocorticoid-induced leucine zipper, referred to as glucocorticoid-induced leucine zipper analogs (GAs), inhibited amyloid β–induced metabolic activity and inflammatory cytokines in mixed brain cell cultures. Here, we investigate the therapeutic efficacy of GA in an Alzheimer's disease model.MethodsG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Moreover, activated microglia can produce ROS as a result of increased production of proinflammatory cytokines, mediating inflammatory tissue damage . Activation of the expression of NF-κB p65 protein was found in the hippocampus in aging and AD models. ,, Herein, we also detected elevated NF-κB p65, COX-2, TNF-α, and IL-1β levels in rats treated with d -gal. Nevertheless, supplementation of d -gal with anthocyanins significantly suppressed the activation of these inflammation factors in rats.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, activated microglia can produce ROS as a result of increased production of proinflammatory cytokines, mediating inflammatory tissue damage . Activation of the expression of NF-κB p65 protein was found in the hippocampus in aging and AD models. ,, Herein, we also detected elevated NF-κB p65, COX-2, TNF-α, and IL-1β levels in rats treated with d -gal. Nevertheless, supplementation of d -gal with anthocyanins significantly suppressed the activation of these inflammation factors in rats.…”
Section: Discussionmentioning
confidence: 54%
“…The NF-κB like other transcription factors substantially regulates the inflammatory and several other pathological processes ( Srinivasan and Lahiri, 2015 ). Since then, NF-κB together with its family members, p50, p52, p65 (Rel-A), Rel-B, and c-Rel proteins, have been discovered to present almost in all forms of animal cells and are involved as a key agent against various stimuli ( Srinivasan Lahiri, et al, 2018 ). Neurotoxicity, oxidative stress, and inflammation are caused by Aβ, which increases progressive neurodegeneration, resulting in nerve damage and neuronal death ( Caruso et al, 2019 ).…”
Section: Inflammatory Mechanism and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Thus, there is an imbalance between the defensive system of cells and the generation of ROS, which in turn lead to cognitive dysfunctions and neurodegeneration ( Reza et al, 2018 ). Moreover, this imbalance also stimulates the expression of several downstream signaling molecules, like mitogen associated kinases (MAPKs) and Protein Kinase-C (PKC), which in turn causes the enhanced expression of proinflammatory cytokines and nuclear translocation of NF-ϏB ( Srinivasan et al, 2018 ).…”
Section: Inflammatory Mechanism and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…The release of GC by the adrenal cortex peaks early in the active phase (morning for diurnal or evening for nocturnal species) to prepare the brain and the body for physical and cognitive activities and reaches nadir in the resting phase (evening for diurnal and morning for nocturnal species). In addition, the GC also exhibit hourly pulses (ultradian rhythm), the amplitude of which is modulated in an activity (daytime) dependent fashion ( Qian et al, 2012 ; Stavreva et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular and animal experiments showed that the ultradian GC treatment induces pulsatile release of GR regulated genes by a process referred to as ‘gene pulsing’ ( Stavreva et al, 2009 ). GR mRNA expression was two-fold higher in the morning than in the evening in human peripheral blood mononuclear cells in correlation with the GC rhythm.…”
Section: Introductionmentioning
confidence: 99%